Association of the BDNF C270T polymorphism with schizophrenia: Updated meta‐analysis. Issue 2 (25th February 2013) - Watanabe, Yuichiro; Nunokawa, Ayako; Someya, Toshiyuki
<x xml:space="preserve">Abstract</x> Brain‐derived neurotrophic factor (BDNF) has been suggested to play a role in the pathophysiology of schizophrenia. The C270T polymorphism (rs56164415) in the BDNF 5′‐non‐coding region has been extensively investigated for an association with schizophrenia, but with conflicting results. An updated meta‐analysis was therefore performed of 13 case–control association studies (3505 patients and 3992 controls). An association was found between the T allele and schizophrenia. The association was significant in the East Asian population, but not in the Caucasian population. It is suggested that the BDNF C270T polymorphism contributes to schizophrenia susceptibility, especially in East Asian subjects.